Phase Equilibrium Study Of Β-Carotene, Tocopherols And Triacylglycerols In Supercritical Fluid Extraction Process From Crude Palm Oil Using Carbon Dioxide As A Solvent - Davernejad, Reza (2010)

(untitled)
Phase equilibrium of the substances from a multi-component system such as crude palm oil in sub and supercritical carbon dioxide solvent has become increasingly important particularly in unit operation processes. In this study, two rigs have been fabricated and calibrated to study the supercritical fluid extraction of β-carotene from crude palm oil and also to evaluate the phase equilibrium of the supercritical extraction of β-carotene, triacylglycerols (TAGs) and tocopherols from crude palm oil using carbon dioxide as a solvent.